Overview of the Continuous Improvement Methodologies used in Organizations - Nicoleta CHICU; Andrei RADUTU (Communications of International Proceedings, 2020)
Nowadays organizations are facing a tremendous wave of change due to various factors such as globalization, technology development, unstable economic environment and specialized workforce. In this context, managers need a series of instruments for obtaining performance in the organizations they are leading, while at the same time, answering to the external and internal factors of change. In order to be able to harmonize these variables, continuous improvement (KAIZEN™) became a performance approach in the economy and motivated all the organizations to think about innovative ways of developing their activities. In this concern, organizations managed to adapt and evolve as customer demands are changing constantly by using continuous improvement techniques at all the levels of the organization on one hand and by keeping in mind that improving processes is a core value of their business on the other hand. Based on literature review and empirical evidence, the aim of this study is to provide an overview of the most used methodologies in continuous improvement, as well to describe the specific characteristics of a project approach within an organization, in order to develop a management system scheme for continuous improvement projects. The method used for this paper is a qualitative one and the purpose of the study is to contribute to an increased understanding of the benefits of such methods and techniques. The paper could be perceived as an initial step in continuous improvement implementation and thereby as a basis for further research studies.
Keywords: Continuous Improvement; KAIZEN™; Evolution; Performance; Management.